A Census of Oxygen in Star-forming Galaxies: An Empirical Model Linking Metallicities, Star Formation Rates, and Outflows - Zahid, H. Jabran (2012)
In this contribution, we present the first census of oxygen in star-forming galaxies in the local universe. We examine three samples of galaxies with metallicities and star formation rates (SFRs) at z = 0.07, 0.8, and 2.26, including the Sloan Digital Sky Survey (SDSS) and DEEP2 survey. We infer the total mass of oxygen produced and mass of oxygen found in the gas-phase from our local SDSS sample. The star formation history is determined by requiring that galaxies evolve along the relation between stellar mass and SFR observed in our three samples. We show that the observed relation between stellar mass and SFR for our three samples is consistent with other samples in the literature. The mass–metallicity relation is well established for our three samples, and from this we empirically determine the chemical evolution of star-forming galaxies. Thus, we are able to simultaneously constrain the SFRs and metallicities of galaxies over cosmic time, allowing us to estimate the mass of oxygen locked up in stars. Combining this work with independent measurements reported in the literature, we conclude that the loss of oxygen from the interstellar medium of local star-forming galaxies is likely to be a ubiquitous process with the oxygen mass loss scaling (almost) linearly with stellar mass. We estimate the total baryonic mass loss and argue that only a small fraction of the baryons inferred from cosmological observations accrete onto galaxies.